Progressive Calcification of Supraspinatus Tendon in Patients With Calcific Tendinitis: Two Case Reports - Mikhail S. Ryazantsev; Aleksandr A. Olchev; Alexey N. Logvinov; Aleksandr V. Frolov; Pavel S. Andreev; Andrey V. Korolev (Travmatologiâ i Ortopediâ Rossii, 2023)
Background. Calcific tendinitis (CT) is a common disease characterized by the presence of calcific deposits in the tendons of the rotator cuff. CT has a wave-like course, and the formed calcification tends to be resorbed. The lysis of the calcium deposits is characterized by a strong pain syndrome, and the site of the calcification is replaced by collagen.